Enhancing Learning, Classroom Engagement, and Attitude through Team-Based Learning among Vietnamese Nursing Students: A Quasi-Experimental Study - Duong Thi Ngoc, Lan; Dao Nguyen Dieu, Trang; Le Van, An; Ho Duy, Binh; Pham Thi Thuy, Vu; Nguyen Truong, Son; Dang Thi Thanh, Phuc; Duong Duc, Hoa; Nguyen Ngoc Quynh, Anh (Pacific Rim International Journal of Nursing Research, 2024)
Due to the increasing number of students each year in Vietnam and elsewhere, current active teaching methods and traditional lecture methods face many difficulties. Therefore, innovation in teaching methods is necessary to meet training needs and ensure training quality. Even though team-based learning is widely used globally, there is still no scientific evidence of the effectiveness of this method in health education in Vietnam. This quasi-experimental study compared individual and team readiness scores and satisfaction in students undergoing team-based learning. The study also compared the effects of the team-based learning method versus traditional lectures on final test scores, classroom engagement, and students’ attitudes toward team-based learning. The study was conducted on 192 fourth-year bachelor of nursing students at the University of Medicine and Pharmacy, Hue University, in the 2022-2023 school year. Students participated in three Nursing Care for Adults with Internal Medicine Disease course modules. Data were collected using five instruments: a Demographic Questionnaire, the Student Preparation Questionnaire, the Classroom Engagement Survey, the Team-Based Learning Student Assessment Instrument, and the Attitudes toward Different Aspects of Team Learning. The data were analyzed using descriptive statistics, independent t-test, and chi-square using SPSS version 20.0. The findings revealed that students in the team-based learning group had mean scores on the team readiness test significantly higher than the individual readiness test in all three modules, and satisfaction with team-based learning was high. When comparing the two groups, the students in the team-based learning classes had significantly higher scores on classroom engagement and more positive attitudes toward this type of learning than those in traditional classes. However, the two groups had no significant difference in final test scores. We recommend that universities in Vietnam urgently consider applying the team-based learning method to many courses for nursing students, given its potential to enhance classroom engagement and foster positive attitudes. However, before widespread application, more research is needed on factors that can affect the effectiveness of team-based learning, such as the capacity of lecturers, teaching assistants, and infrastructure conditions. More extensive research in more courses, more students, and longer periods are needed to see the long-term benefits of team-based learning.